2021
DOI: 10.1002/smll.202106100
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Strategy of Combinational Blow Toward Enhanced Cancer Chemo‐Photodynamic Therapy via Sustainable GSH Elimination

Abstract: Excessive glutathione (GSH), which is produced owing to abnormal metabolism of tumor cells, scavenges photo‐induced reactive oxygen species (ROS) and consumes chemotherapeutic drugs, thereby attenuating the efficacy of photodynamic therapy and chemotherapy, respectively. Predominant strategies for GSH inhibition involve its chemical depletion, which only leads to a temporary therapeutic effect because GSH is replenished via various compensatory routes in tumor cells. Here, a versatile GSH‐inhibiting nanosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…Briefly, cells were seeded (5 × 10 3 cells per well) in 96-well plates and cultured for 24 h in a final volume of 100 µL. The cells were further incubated with blank DMEM or increasing concentrations of DHA (5,10,20,40,80,160,320, and 640 µm) for 24 h. MTT solution (20 µL, 5 mg mL −1 ) was added and incubated for another 4 h. After discarding the medium and 150 µL DMSO was added to each well. The absorbance was measured by a Versamax microplate reader at 495 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, cells were seeded (5 × 10 3 cells per well) in 96-well plates and cultured for 24 h in a final volume of 100 µL. The cells were further incubated with blank DMEM or increasing concentrations of DHA (5,10,20,40,80,160,320, and 640 µm) for 24 h. MTT solution (20 µL, 5 mg mL −1 ) was added and incubated for another 4 h. After discarding the medium and 150 µL DMSO was added to each well. The absorbance was measured by a Versamax microplate reader at 495 nm.…”
Section: Methodsmentioning
confidence: 99%
“…[ 4 ] The generation of reactive oxygen species (ROS) is one of the main mechanisms for emerging anti‐cancer strategies. [ 5,6 ] Under physiological conditions, cells control the level of ROS by using the scavenging system to balance the ROS production and elimination. Excessive ROS can damage DNA, proteins, and lipids of cells, leading to cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al reported a versatile GSH-inhibiting nanosystem (PCNPs) for persistent synergistic therapy of cancer. 112 PCNPs not only demonstrated a prolonged release of buthionine sulfoximine to sustainably suppress the biosynthesis of GSH and improved drug utilization for efficient chemotherapy, but also acted as an efficient photo-induced singlet oxygen radical generator that prevents the loss of ROS, enhancing photodynamic therapy. Diselenide-rich polymers were developed for redox-responsive drug delivery as well.…”
Section: Delivery Systems Of Chemo/pdt Synergistic Treatmentmentioning
confidence: 99%
“…Glutathione (GSH), an intracellular tripeptide, has been considered a critical modulator for tumor initiation, progression, and metastasis. , Moreover, GSH is involved in the resistance to many therapeutic approaches, including reactive oxygen species (ROS)-based therapy, immunotherapy, and chemotherapy. In light of this, consumption of intracellular GSH is recognized as a potent strategy to combat cancer. Another important role of GSH in cells is to maintain redox homeostasis.…”
Section: Introductionmentioning
confidence: 99%